New Strategies in Sarcoma: Linking Genomic and Immunotherapy Approaches to Molecular Subtype - Jamie Lim; Neal Poulin; Torsten O. Nielsen (2015)
There are more than 100 sarcoma subtypes, each uncommon and diagnostically challenging. Conventional chemotherapy has little benefit for most soft-tissue sarcomas; new treatment strategies are needed. Multiple recent genomic studies have provided detailed insights into sarcoma biology, including more accurate classification by molecular subtype, identification of recurrent mutations in oncogenic pathways, and evidence of epigenetic dysregulation. Advances in immunotherapy (adoptive immune cell transfer, tumor vaccine strategies, and immune checkpoint inhibition) have also provided a better understanding of how immuno-oncology might best be applied to sarcoma treatment, including connections to oncogenic pathways that may support combination strategies with conventional and targeted therapies. In this article, we review the latest sarcoma genomic studies and immuno-oncology developments and discuss how the findings suggest potential strategies to improve diagnosis and treatment across multiple sarcoma subtypes.